Assessment of Human Development Status and Personal Ecological Footprints of Residents of Ile-Ife, Nigeria - Ojedokun, Olalekan Elijah; Elugoke, Nicholas Olaniyi (European Journal of Sustainable Development, 2016)
This study assessed the human development status (level of education, health and standard of living) – HDI, and personal ecological footprints (indicated by food consumption pattern, frequency of travel, energy consumption, strength of home installations and environmental friendliness of purchased life supporting materials) – PEFP of residents of Ile-Ife, Osun State, Nigeria and determined the relationship that existed between these two variables. These were with the view to providing a baseline information that could guide further studies on how to reconcile human development with ecological sustainability of Nigerians, especially those of the educational advantaged Southwestern Nigeria. The study employed the survey research design to collect data on human development status (HDS) as a measure of HDI, and the PEFP of the respondents to the study. The data collected were analysed using the arithmetic mean, Geographic Information System packages and correlation statistics. The results showed that the residents’ HDI of 0.68 was higher than the United Nations developmental categorization of 0.5 for Nigeria; their personal ecological footprint was not statistically significant (2.45 ± 0.18, p>0.05); and the relationship between the Human Development Status and Personal Ecological Footprints of residents was not statistically significant (r = 0.31, p>0.05). It concluded that further studies will be needed to confirm this study in the educationally advantaged Southwestern Nigeria on a larger scale. Keywords: Assessment; Human Development Status; Personal Ecological Footprints; Residents; Ile-Ife; Nigeria